Assault predicts time away from work after claims for work-related mild traumatic brain injury. Issue 7 (24th May 2019) - Shafi, Reema; Smith, Peter M; Colantonio, Angela
Abstract : Introduction: Workplace violence carries a substantial economic loss burden. Up to 10% of all traumatic brain injury (TBI) admissions result from physical assault. There remains a paucity of research on assault as a mechanism of injury, taking into account sex, and its association with work re-entry. Objectives: The aim of this study was to characterise, by sex, the sample of workers who had sustained a work-related mild TBI (wr-mTBI) and to assess the independent influence of assault, as a mechanism of injury, on time away from work. Methods: A population-based retrospective cohort of workers' compensation claimants in Australia (n=3129) who had sustained a wr-mTBI was used for this study. A multivariable logistic regression analysis assessed whether workers who had sustained wr-mTBI as a result of assault (wr-mTBI-assault) were more likely to claim time off work compared with workers who had sustained a wr-mTBI due to other mechanisms. Results: Among claimants who sustained a wr-mTBI, 9% were as a result of assault. The distribution of demographic and vocational variables differed between the wr-mTBI-assault, and not due to assault, both in the full sample, and separately for men and women. After controlling for potential confounding factors, workers who sustained wr-mTBI-assault, compared with other mechanisms, were more likely to take days off work (OR 2.14, 95% CI 1.53 to 2.99) within a 3-month timeframe. Conclusion: The results have policy-related implications. Sex-specific and workplace-specific prevention strategies need to be considered and provisions to support return-to-work and well-being within this vulnerable cohort should be examined.